Analyzing and Formulating a Statutory General Anti-Avoidance Rule (GAAR) in Indonesia - Wijaya, Suparna; Kusumaningtyas, Dewi Sekarsari (Jurnal Ilmiah Akuntansi dan Bisnis, 2020)
Dealing with the practice of tax avoidance in general, many countries have compiled and implemented their own general anti-avoidance rules (GAAR). This research aims to explore the potential of statutory GAAR in handling tax avoidance practices in Indonesia and SAAR formulas that are suitable for the Indonesian context. This qualitative research employed a case study approach. Results show that the application of SAAR and the principle of substance over form in Indonesia cannot yet be applied properly; thus GAAR is needed. It is expected that the implementation of statutory GAAR can accommodate the limitations of regulators in light of unknown and future tax avoidance schemes.. Keywords: Tax-avoidance, tax planning, specific anti avoidance rule (SAAR), international tax